Answer:
(4x3-6x) + (8x-12)= 2x
(4x3+8x) + (-6x2-12)= 2(2x-3) (x^2+2)
Step-by-step explanation:
All you have to do is simplify.
The intersection of the two sets is the list of members that appear in both sets. That is {3}.
Your statement is FALSE.
Answer:
im sorry cant help
Step-by-step explanation:
It gave you the input because it is telling you what x is
Answer: n = -6
Step-by-step explanation:
3n+14=-4
Subtract 14 from both sides.
3n+14-14=-4-14
Simplify
3n=-18
Divide both sides by 3
3n/3 = -18/3
n=-6